Optimización de rutas de lecturas de consumo de agua potable para el sistema de recaudación del GAD Guano utilizando Pgrouting en QGIS - Gordón Villa, Karina Alexandra (2019)
In this research work, QGIS is proposed, which is a geographic information tool that provides a growing range of basic functions and complements, in addition to being able to visualize, manage, edit and analyze data. In the first place, a system with the appropriate functions that allows the collection of water according to the user's consumption or optimized routes was not available. The study proposed the use of the PGrouting plugin in the QGis tool to achieve a correct optimization of the routes for taking readings anywhere and also to improve the activity carried out by the people in charge of taking readings of the drinking water consumption of the canton. The products generated through the investigation are the representation of the optimal route on the Guano Canton map through the use of the pgRouting plugin within the Geographic Information System called QGis. Another of the products generated is the Potable Water collection system called SOGESLEC.